BIOMASS ANALYSIS FOR COMBUSTION APPLICATIONS – CASE STUDY SCENARIOS - NENU, Petre Florinel; DUNGAN, Luisa Izabel; CIOABLĂ, Adrian Eugen; RUSU, Gerlinde; BANDUR, Geza Nicolae; DUMITREL, Alina Gabriela; PODE, Vasile (Studia Universitatis Babeș-Bolyai Chemia, 2018)
Nowadays the need for renewable resources becomes more and more stringent. Biomass remains one of the most important sources of energy, being used directly or by chemical conversion processes in order to produce clean energy. Relative to this aspect, the present paper proposes the direct approach, by analyzing to biomass type materials (topinambur and Romanian hemp) in order to determine their physical and chemical characteristics and their potential use in combustion processes.